Bone marrow niche in the myelodysplastic syndromes. Issue 10 (October 2015) - Cogle, Christopher R.; Saki, Najmaldin; Khodadi, Elahe; Li, June; Shahjahani, Mohammad; Azizidoost, Shirin
Highlights We discuss important stomal cells in the MDS BM niche. We discuss important cytokines in the MDS BM niche. We Identify opportunities for further study of the MDS BM niche.